Síntese e processamento de titânia nanoestruturada - Roca, Román Alvarez (Universidade Federal de São Carlos, 2013)
The TiO2 is widely used in several applications. In recent times these applications have been enhanced with the use of the nanotechnology. In this work, the sol-gel synthesis process, at low temperature, of TiO2 nanoparticles was investigated. The synthesis used TiCl4 as precursor in different solvents (Octanol, Ethanolamine and Terathane) and the products were characterized by X-Ray Diffraction (XRD), Gas Absorption (BET), Thermoanalytic Techniques (ATG, DSC) and Transmission Electron Microscopy (TEM). XRD and TEM showed the crystallite size ranging from 4 to 16 nm and different particles morphologies and phase compositions (amorphous, anatase pure, and anatase/rutile mixture) were also shown. TEM images displayed variations in the morphological behavior depending on the synthesis condition. Between these morphologies nanostructures (1D and 3D), which are primaries nanoparticles self-assembled by oriented attachment, can be observed. The ceramic processing of these nanopowders is also investigated from the compacting, densification and sintering behavior. The compressibility curve shows a typical behavior of agglomerates. The densification process was investigated by the dilatometric analysis using nonisothermal experiments. The densification parameters were determinate and the grain boundary sliding assisted by surface diffusion was proposed as the dominant shrinkage mechanism. Different sintering methods are applied (SC, TSS and fast firing). The microstructure, by SEM, is analyzed and confronted with previous results. This work showed that the TiO2 nanoparticles could be easily engineered and adapted by the solvent type, the TiCl4 concentration and the synthesis time. The principal processes of the synthesis and processing are dependents strongly of the high agglomerate state of the nanopowders.
Synthesis and processing of titania nanostructured
Keywords: Materiais nanoestruturados; Cerâmica; Titânia; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA